Reliability of the Biomechanical Assessment of the Sagittal Thoracic Spine on Radiographs Used in Clinical Practice: A Systematic Literature Review - Joseph W. Betz; Douglas F. Lightstone; Jason W. Haas; Paul A. Oakley; Joseph R. Ferrantelli; Ibrahim M. Moustafa; Deed E. Harrison (Bioengineering, 2026)
Background: Measurement reliability of the sagittal thoracic spine, e.g., thoracic kyphosis and balance, on radiographs has an unknown evidence base. This literature review aims to systematically identify and evaluate the reliability of biomechanical assessments of the sagittal thoracic spine on radiographs used in clinical practice. Methods: The study design was registered with PROSPERO (CRD42023431171). Chiropractic Biophysics Nonprofit, Inc (Eagle, ID, USA) funded this investigation. Inclusion criteria involved studies in English using human subjects, radiography, and reliability analysis of biomechanical analysis of the thoracic spine. Exclusion criteria involved animal and cadaveric studies, phantom mannequins, geometric studies, and non-radiographic studies. This review was conducted using the Peer Review of Electronic Search Strategies (PRESS) checklist to organize the search strategy. A combined approach using Medical Search Headings (MeSH) search terms and a systematic literature review (SLR) search strategy was used. This review followed the recommendations of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Databases searched included PubMed, CINAHL, Alt HealthWatch, Web of Science, and a grey literature search. Initial search results produced 990 results. A total of 658 records were screened by two independent reviews and 197 full text articles were assessed for eligibility. Results: Sixty-six studies were included in the final analysis and assessed for methodological quality and bias using the 11-item Quality Appraisal of Diagnostic Reliability (QAREL) tool. A total of 15 studies were of low methodological quality (high risk of bias), 28 were of moderate quality (moderate risk of bias), and 23 were of high quality (low risk of bias). Conclusions: This SLR found most articles investigating the reliability of biomechanical assessment of the sagittal thoracic spine on radiographs to be of moderate-to-high quality and show good-to-excellent reliability.